WUJUD LOKALITAS BUDAYA NOVEL SILARIANG CINTA YANG (TAK) DIRESTUI KARYA OKA AURORA - Hariyono, Saharul; Fitriani, Hilma Nurullina (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2023)
Literary sociology developed rapidly in the 18th century or since research using the theory of structuralism was considered to have experienced stagnation and was even considered involution. Literary sociology tries to present what is neglected structurally, namely the relevance of society. Literary sociology connects the experiences of fictional characters and situations created by the author, with the historical conditions of their origin. Therefore, this research aims to utilize sociological literature studies to describe the Buginese community's cultural localities in the novel Silariang Cinta Yang (Tak) Direstui by Oka Aurora. The data analysis technique used includes how the sociology of literature analysis model works, such as analyzing social problems contained in the work itself, and then connecting them with the real world which is generally considered extrinsic-reflective. Then find the relationship between structures that are dialectical in nature. This way of working then produces research that is intertwined with cultural forms silariang, siri', mabbaratta, mappadeceng, art, get closer to God.